Chile : New Economy Study, Volume 2. Background Documents - World Bank (Washington, DC, 2013)
The report comprises two volumes, the Executive Summary and Policy Recommendations (Volume 1), and the Background Documents (Volume 2), providing the scope, and organization of the study as follows. The first chapter assesses the performance of Chile in the knowledge economy, where knowledge is a critical factor for competitiveness and growth. It examines progress to date, and remaining challenges with respect to three factors - the knowledge variables: 1) the economic incentive and institutional regime; 2) science and technology; and, 3) the education system. The second chapter looks at Chile's Information and Communication Technology (ICT) - the infrastructure of the knowledge economy. The third chapter evaluates the potential use of ICT by local firms, with special focus on micro, small and medium businesses (MSMBs), which represent the bulk of the Chilean productive sector. The focus of the overall analysis is on the role of Knowledge in improving the productivity of the private sector. The study's main focus on improving productivity of the private, rather than the public sector, is motivated by the fact that a recent Bank Public Modernization loan, addresses key issues in improving the effectiveness, and efficiency of the Chilean public administration. It is highlighted that the recent growth of the Chilean economy, and positive short-term outlook, should not deter the Government from embarking on further reforms aimed at improving the productivity of the private sector. Chile may want to encourage microeconomic reforms supporting private sector development. Recommendations include the creation of innovative businesses, a single contact point for business registration, and a more flexible labor market, so as to reduce the costs of labor, increase employment, and that of firm's productivity. Moreover, the Government should review, and rationalize its programs in support of science, technology, and innovation, encouraging private participation in science, to ensure an adequate, relevant research, and, promote further reforms to improve the quality of education. Such policy agenda will require public-private partnerships to enhance productivity, and growth, which will require rethinking some economic principles.